Biomarkers for tuberculosis: the case for lipoarabinomannan. Issue 1 (11th February 2019) - Correia-Neves, Margarida; Fröberg, Gabrielle; Korshun, Liudmyla; Viegas, Sofia; Vaz, Paula; Ramanlal, Nehaben; Bruchfeld, Judith; Hamasur, Beston; Brennan, Patrick; Källenius, Gunilla
Tuberculosis (TB) is considered the most onerous of infectious diseases according to recent reports from the World Health Organization. Available tests for TB diagnosis present severe limitations, and a reliable point-of-care (POC) diagnostic test does not exist. Neither is there a test to discern between the different stages of TB, and in particular to predict which patients with Mycobacterium tuberculosis infection and no clinical signs are more at risk of advancing to overt disease. We here review the usefulness of mycobacterial lipoarabinomannan (LAM) as a diagnostic marker for active and latent TB and, also, aspects of the immune response to LAM relevant to such tests. There is a high potential for urinary LAM-based POC tests for the diagnosis of active TB. Some technical challenges to optimised sensitivity of the test will be detailed. A method to quantify LAM in urine or serum should be further explored as a test of treatment effect. Recent data on the immune response to LAM suggest that markers for host response to LAM should be investigated for a prognostic test to recognise individuals at the greatest risk of disease activation. There is a high potential for a urinary LAM-based point-of-care test to diagnose TB. Markers for host response to LAM should be explored to identify those at highest risk of developing active TB. http://ow.ly/FyCs30n4uFE